Integrated fuel cell processor for a 5-kW proton-exchange membrane fuel cell - Ratnamala, G. M.; Shah, N.; Mehta, V.; Rao, P. V.; Devotta, S. (Industrial & Engineering Chemistry Research, 2005)
A fuel processor is a combination of a few reactors to generate hydrogen required for a fuel cell. The study deals with the production of hydrogen suitable for a 5-kW proton-exchange membrane fuel cell (PEMFC) for household applications using liquefied petroleum gas (LPG) as the fuel. The aim is to energy integrate the five reactors in a fuel processor, i.e., desulfurizer, steam reformer, high-temperature shift reactor, low-temperature shift reactor, preferential oxidation reactor, and various heat exchangers. Heat-exchanger network synthesis analysis has been carried out for the entire process to make the process efficient. The results obtained from the studies show that the steam reforming with LPG gives a higher concentration of hydrogen in the product of about 74%. The fuel cell efficiency is around 34%, and the thermal efficiency including lean gas is about 93%. The model developed can serve as the basis for the development of an integrated PEMFC decentralized power pack for household applications.